Assessment of the antibacterial capacity of extracts of sinapis alba l. By the method of plates and wells (2019)
The antibacterial effect of the essential oils of Sinapis alba L is known, since these contain mainly allylisothiocyanate, with an inhibitory effect on a great variety of bacteria. This study was carried out to known the antibacterial effects of Sinapis alba L. extracts to three different bacteria strains. The plates and wells methodology was used.The results allowed to determine that all the vegetal organs of Sinapis alba had an inhibitory effect to S. aureus, however, no evidence inhibitory effect against E. coli or Pseudomonas. And the highest percentage of inhibition was with petroleum ether solvent.